20. The value of (a + 1) (a - 1)(a + 1) is (a" - 1). true or false
Answers
Answered by
2
Step-by-step explanation:
Given, (a+1)(a−1)(a2+1).
We know, (a+b)(a−b) =(a2−b2).
Multiply by using direct method, we get,
(a+1)(a−1)(a2+1)=[a2−12](a2+1)
=(a2+1)(a2−1)
Now, by using formula (a2−b2)=(a+b)(a−b), we get,
=((a2)2−(1)2)
=a4−1.
hope it helps uh!
plz mark as brainliest answer
Similar questions
English,
2 months ago
English,
2 months ago
Math,
2 months ago
Computer Science,
5 months ago
Computer Science,
5 months ago
Chemistry,
1 year ago